گ̑چەلى سێكسى له ديدو بۆچونى كچه خوێدكارانى زانكۆى سلێمانيەوە - فتاح, بەختيار ابراهيم; عبداه, عادل محمد نورى (Sulaimani Journal for Humanities, 2025)
Harassment as a social problem dates back to the old times and societies in general face this problem constantly, particularly the backward and closed societies of the East. Harassment is a dangerous phenomenon that spreads quickly and under numerous names and pretexts such as equality, civilization and prosperity. Thereupon, the present study attempts to approach the phenomenon from a sociological perspective assuming that ‘harassment’ is a social act and behavior arising from the contexts of daily interactions of the individuals.So, the study offers an appropriate theoretical framework to study sexual harassment among male and female students and also to identify the goals the doer seeks to achieve by committing the act. In Kurdistan region, the female students belong to a disadvantaged segment oppressed by the instructors, employees and others inside the university and men from outside the campus and are prone to violence and various kinds of harassment which impact the educational and cultural standards of the female students.Moreover, there are some social values which are deep rooted in the human mind such as when the man views women as if they were inferior and worth despise and contempt.Hence, covering the victims of harassment is relatively easy since acquiring concrete evidence can be hard and thereby the victim will lose the case.So, the criminalization of harassment aims at protecting women’s honor and sexual freedom.Even though gratifying sexual desire is a natural right of every human being, the authorities must be committed to protect human rights in all their aspects and faces. Thus, we have concluded the topic by stating that harassment is any word, act, reference or behavior of an unfavorable nature such as verbal harassment, criminal behavior and sexual aggressions against the will of the victim or under duress. It should be noted that the nature of this study involved the analytical descriptive approach aiming at exploring the phenomenon of sexual harassment in the Kurdish society in general and the universities in particular in addition to the causes of the phenomenon in all its forms and aspects.The samples of the study were taken randomly from the female students of the same college.250 students were taken from all the departments.Then, a questionnaire was distributed among them that contained 35 questions. Finally, the results were drawn and recommendations and suggestions for further studies have been listed at the end of the study